Explanation:
f(a):
So for this you simply plug in "a" as x, and this doesn't really do anything beside replace all values with x, so you just have the equation:
![f(a) = 5a+4](https://img.qammunity.org/2023/formulas/mathematics/high-school/anpiezslkaj41f0x2fsm5rmmf7392zpa17.png)
2 f(a):
So for this one, you want to represent f(a) using the equation it's equal to (5a + 4), and substitute it in for f(a). In doing so, you get the expression:
2*f(a) -> 2(5a + 4) -> 10a + 8
f(2a):
So this is very similar to the first question, although you will have to do some multiplication. So just plug in 2a as "x" to get the equation:
![f(2a) = 5(2a) + 4 = 10a+4](https://img.qammunity.org/2023/formulas/mathematics/high-school/m9ierck4m81qultu8hs2hwfo5pce7fl3x1.png)
f(a+2):
Basically the same process, you plug in (a+2) as "x" and simplify:
![f(a+2) = 5(a+2) + 4\\f(a+2) = 10a+10+4\\f(a+2) = 10a+14](https://img.qammunity.org/2023/formulas/mathematics/high-school/nh8z7ci0pv0shbnpt0cjahlzfgmr18nad1.png)
f(a) + f(2):
This is similar to the second question, and you simply want to replace the f(a) with the equation that represents it (5a + 4) and same thing for f(2) = 5(2) + 4
![f(a) + f(2) = (5a+4)+(5(2)+4) \\f(a) + f(2) = (5a+4)+(10+4)\\f(a)+f(2) = (5a+4) + (14)\\f(a) + f(2) = 5a+18](https://img.qammunity.org/2023/formulas/mathematics/high-school/chso26y2t8llh30gk0ru0zbaaeysylop8o.png)